Effectiveness of Self-Compassion Intervention on Criminal Thinking in Male Prisoners - Rezapour-Mirsaleh, Yasser (International journal of offender therapy and comparative criminology, 2021)
This study aimed to investigate the effectiveness of self-compassion intervention on criminal thinking in male prisoners. A quasi-experimental design utilizing pre-test, post-test, and follow-up test and waiting-list control groups was conducted. A total of 24 male prisoners were selected by purposeful sampling and randomized into experimental and waiting list control groups. Participants of experimental group received eight sessions of self-compassion intervention; and all participants answered to psychological inventory of criminal thinking styles (PICTS) as dependent variable at three time points (pre-test, post-test, and 2-month follow-up). A repeated measures analysis of variance was used to analyze the data. Results showed criminal thinking was significantly decreased in experimental group, as compared to control, at post-test phase (p < .01); and improvement of criminal thinking in the follow-up phase has also been continued (p < .05). Therefore, to reduce criminal behaviors or rehabilitation of prisoners, self-compassion based intervention can be used.